Kinetic study of adsorption methylene blue dye from aqueous solutions using activated carbon - Fatima Zahra Benhachem; Tarik Attar; Fouzia Bouabdallah (Chemical Review and Letters, 2019)
In this article efficiency of activated carbon as a potent adsorbent of cationic dyes dyes present in waste water was studied in this research. Activated carbon (AC) from starch was used to adsorb methylene blue (MB) from an aqueous solution. Various parameters such as adsorbent concentration, temperature, initial dye concentration, contact time, and pH were investigated and the optimum parameters were determined based on the experimental outcomes. The extent of methylene blue removal increased with the increased in contact time, adsorbent mass, solution pH and amount of adsorbent used. Thermodynamic parameters like the Gibbs free energy (ΔG°), enthalpy (ΔH°), and entropy (ΔS°) were also determined and they showed that the adsorption process was feasible, spontaneous, and exothermic in the temperature range of 293–333 K. The experimental equilibrium data were analyzed using the isotherms of Langmuir, Freundlich, and Tempkin. Two simplified kinetic models including pseudo-first-order and pseudo-second-order equation were selected to follow the adsorption processes.